Perbandingan Hasil Belajar Kognitif Peserta Didik Melalui Pembelajaran Guided Discovery dan Guided Inquiry pada Materi Kesetimbangan Kimia - Winda Fajriati; Zonalia Fitriza (Edukimia, 2020)
The purpose of this research is to compare the student’s result study who learn using Guided Discovery models and Guided Inquiry models. The research sample is 2 classes XI Science in one of the high schools at SMAN 9 Padang, sample class 1 is the Guided Discovery model treatment and sample class 2 is with the Guided Inquiry model. The research design was Randomized Posttest-Only Comparison Controls Groups Design. The instrument in the study was the learning achievement test (posttest). The results of the study stated that: (1) learning outcomes with the Guided Discovery and Guided Inquiry models there were differences, but not significant. Evidenced by the averages student’s result study of the two classes that have a slight difference, namely sample class 1 (81.86) while sample class 2 (84.36). (2) The results of the statistical test of hypothesis testing with the t test (α = 0.05) obtained tcount = 0.65 and ttable = 1.99. The results show thats the Guided Discovery and Guided Inquiry models effectively improve student learning outcomes.